How effective is an integrated approach to low vision rehabilitation? Two year follow up results from south Devon. Issue 8 (August 1995) - Shuttleworth, G N; Dunlop, A; Collins, J K; James, C R
Abstract : AIMS--A survey was undertaken to assess the effectiveness of an integrated approach to the provision of low visual aids (LVAs) in south Devon over a 2 year follow up period. This integrated approach includes the assessment of patient needs by low vision therapists, followed by the provision of suitable LVAs, with particular emphasis on training in their use. METHODS--A total of 125 patients were selected at random from the 445 patients seen in the low vision clinic at Torbay Hospital in the year 1991. These patients were sent questionnaires relating to the service over a 2 year period. Questionnaires from 111 patients were analysed at 1 year and 75 questionnaires together with 46 clinical reassessments, after 2 years. RESULTS--Using a similar questionnaire to one used in a previous study in the UK from a unit where LVA training was not provided, not only was a higher rate of satisfaction found with the services provided, but also the LVAs dispensed were used more frequently. The majority of the LVAs provided were of the simple, inexpensive variety and wastage was very low. CONCLUSIONS--It was concluded that this integrated approach to low vision rehabilitation with emphasis on training in the use of less complex LVAs exceeds the performance of other types of service that rely on the dispensing of more complex LVAs.